2018
DOI: 10.1177/1754073918798089
|View full text |Cite
|
Sign up to set email alerts
|

Concluding Commentary: Schadenfreude, Gluckschmerz, Jealousy, and Hate—What (and When, and Why) Are the Emotions?

Abstract: Schadenfreude, gluckschmerz, jealousy, and hate are distinctive emotional phenomena, understudied and deserving of increased attention. The authors of this special section have admirably synthesized large literatures, describing major characteristics, eliciting conditions, and functions (Chung & Harris, 2018; Fischer, Halperin, Canetti, & Jasini, 2018; R. H. Smith & van Dijk, 2018). We discuss the contributions of each article as well as the issues they raise for theories of emotions and some remaining questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
1
9
0
1
Order By: Relevance
“…Considerable theorizing has described what hate is, how it develops, how it relates to other discrete emotions, and what its cognitive, motivational, and behavioral characteristics are (e.g., Allport, 1954; Brewer, 1999; Fischer et al, 2018; Kucuk, 2016; Royzman et al, 2005; Staub, 2005; Sternberg & Sternberg, 2008). Nevertheless, research testing this theorizing empirically is remarkably scarce (Halperin et al, 2012; Royzman et al, 2005; Sternberg & Sternberg, 2008), and only a handful of studies have focused on the differences between hate and other emotional experiences such as anger, fear or dislike (Fischer et al, 2018; Halperin, 2008; Roseman & Steele, 2018; Van Bavel et al, 2018).…”
Section: The Nature and Distinctive Properties Of Hatementioning
confidence: 99%
See 1 more Smart Citation
“…Considerable theorizing has described what hate is, how it develops, how it relates to other discrete emotions, and what its cognitive, motivational, and behavioral characteristics are (e.g., Allport, 1954; Brewer, 1999; Fischer et al, 2018; Kucuk, 2016; Royzman et al, 2005; Staub, 2005; Sternberg & Sternberg, 2008). Nevertheless, research testing this theorizing empirically is remarkably scarce (Halperin et al, 2012; Royzman et al, 2005; Sternberg & Sternberg, 2008), and only a handful of studies have focused on the differences between hate and other emotional experiences such as anger, fear or dislike (Fischer et al, 2018; Halperin, 2008; Roseman & Steele, 2018; Van Bavel et al, 2018).…”
Section: The Nature and Distinctive Properties Of Hatementioning
confidence: 99%
“…Hate has been linked to attack action tendencies ranging from verbal aggression and hate speech to moral exclusion, physical aggression, and extreme violence (Chetty & Alathur, 2018; Opotow & McClelland, 2007; Sternberg, 2003). Alternatively, other studies have suggested instead that hate’s broader goal is to keep the targets out of one’s life, associating hate to avoidance-oriented action tendencies (Aumer & Bahn, 2016; Roseman & Steele, 2018). The distinctive action tendencies of anger, contempt, and disgust are less controversial.…”
Section: The Nature and Distinctive Properties Of Hatementioning
confidence: 99%
“…Each article examines the antecedent conditions, appraisals, motivations, action tendencies, and functions of these affective states and compares them to closely related emotional states. The nature of these states is further considered in the concluding piece by Roseman and Steele (2018), who cogently chart out how jealousy, hate, schadenfreude , and gluckschmerz compare to potentially related emotions (joy, distress, fear, and anger). Other comments also raise intriguing possibilities about the function (e.g., van de Ven, 2018; van Doorn, 2018) of these states as well as the utility of studying them even if they are not distinct emotions (Hess, 2018).…”
Section: Themes and Challengesmentioning
confidence: 99%
“…Each of the target articles is accompanied by two comments along with author replies. The final piece (Roseman & Steele, 2018) analyzes all three target articles and serves as a conclusion to the special section.…”
Section: The Articlesmentioning
confidence: 99%
“…Guilt has not been found to have a unique facial or bodily nonverbal expression but recent evidence suggests that people may frown, touch their necks, and try to repair when feeling guilty (Julle-Danière et al, 2020). Similarly, jealousy does not have a unique facial or bodily expression but may be expressed through bids for attention, putting oneself between a rival and loved one, surveillance, and aggression (Roseman and Steele, 2018).…”
mentioning
confidence: 99%